PRAGMATIC ANALYSIS OF THE POLITENESS STRATEGIES USED IN THE DIRECTIVE SPEECH ACTS IN PAPUA NEW GUINEA’S NATIONAL PARLIAMENT SITTING SESSION ON MAY 30TH 2024 - Andreas Noreewec (Prodi Sastra Inggris UKI, 2024)
Abstract This study presents a pragmatic analysis of the politeness strategies employed in directive speech acts during the Papua New Guinea National Parliament sitting session on May 30th, 2024. Utilizing Brown and Levinson's politeness theory as the analytical framework, the research examines how members of parliament navigate face-threatening acts through linguistic strategies to maintain social harmony and achieve political goals. Data for the study were collected from the official parliamentary transcripts, focusing on instances of directives such as requests, commands, and suggestions. The analysis reveals a predominance of negative politeness strategies, reflecting a high sensitivity to hierarchical structures and the desire to mitigate imposition. Additionally, the study identifies contextual factors, such as the socio-political environment and cultural norms, influencing the choice of politeness strategies. The findings contribute to a deeper understanding of the intersection between language, power, and culture in parliamentary discourse, offering insights into the pragmatic dynamics of political communication in Papua New Guinea. This research underscores the importance of context in the pragmatic realization of politeness and highlights the role of language in shaping political interactions within legislative settings. Keywords: Politeness strategies, Directive speech acts, Papua New Guinea National Parliament